PETROMAGNETISM AND PALAEOMAGNETISM OF SUBAERIAL DEPOSITS OF BOYANYCHI AND KORSHIV SECTIONS (VOLHYNIAN UPLAND) - Hlavatskyi, D.; Bakhmutov, V.; Bogucki, A.; Voloshyn, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A petromagnetic and palaeomagnetic research of Boyanychi and Korshiv loess-paleosoil sequences (Volhynian Upland) were carried out. The distributions of magnetic parameters along lithostratigraphy column (natural remanent magnetization, magnetic susceptibility, anisotropy of magnetic susceptibility parameters) are presented. Variations of magnetic parameters do not correlate with lithology and cannot be attributed to the "alaskian" or the "chinese" type of subaerial deposits. The rocks are characterized by high stability to alternating magnetic field demagnetization and temperature demagnetization due to the presence of highly coercive magnetic mineral (probably hematite). Both loess and soils have mainly primary sedimentary magnetic texture. The characteristic component of magnetization has only normal polarity and no samples with reverse polarity. In the bottom of the sections the Matuyama-Brunhes boundary was not recognized, that prove the formation of deposits occurred during normal polarity Brunhes zone no later than 780 kyr.